OVERCOMING LEGAL BARRIERS: ENSURING JUSTICE FOR PERSONS WITH DISABILITIES VICTIMIZED BY SEXUAL VIOLENCE - Natalis, Aga; Surayda, Helen Intania (Revista Direito e Sexualidade, 2024)
There are several cases of sexual violence experienced by Persons with Disabilities, unfair and discriminatory justice that afflicts Persons with Disabilities. In the judicial process, often, Persons with Disabilities are blamed by law enforcement for their identity Persons with Disabilities. Based on the above problems, the purpose of this study is to know, find, and analyse the obstacles faced by escorts and Persons with Disabilities during access to legal aid when Persons with Disabilities experience sexual violence and to know, find, and analyse the model of access to fair legal aid for Persons with Disabilities as victims of sexual violence. The research uses empirical juridical approach methods. The results showed that the obstacles faced by escorts and Persons with Disabilities in accessing fair legal aid at a time when disability is a problem that occurs in service institutions, constraints on Persons with Disabilities, and constraints on law enforcement officials. From these constraints, it can be created a model of access to fair legal aid for Persons with Disabilities victims of sexual violence, such as legal assistance services in the form of complaints at the police level to the courts following the conditions of victim disabilities. Therefore, it takes a discussion room with law enforcement officials, criminal law experts who understand gender justice, and legal escorts to equate perceptions of law enforcement for Persons with Disabilities victims of sexual violence, especially with various mental and intellectual disabilities.